PARTICLE MODEL ON INFLUENZA DISEASE TRANSMISSION - PUSPITASARI (10112081), FANI
Influenza disease problem is a complex issue with many factors involved. Some of these factors include the uncertain climate change, human mobility and spatial heterogeneity factor. In simplifying the complexities, mathematical models that are often constructed to describe the spread of a disease is a SEIR deterministic model or SIR deterministic model. However, there are some weakness of these deterministic models, such as the health status of each individual in the same compartment is considered equal and the probability of contact between individuals in the population is also considered the same as ignoring the distance between individuals. By involving the assumption of spatial heterogeneity, a mathematical model that is built to describe the spread of influenza is a particle model, which in this model every human being is seen as a particle and the human population is seen as a particle system. Furthermore, we construct the particle model of influenza with vaccination that is analyzed in comparison with the particle model without vaccination. In addition, the value of the parameter of interaction between individuals is also estimated to estimate the Basic Reproductive Ratio from influenza particle model. The results of the simulation of the particle model on influenza disease transmission are shown with the spatial heterogeneity factors: distance and the health status which influence the effect of interaction between individuals.